Potensi Kompos Kombinasi Eceng Gondok (Eichhornia crassipes) dan Azolla (Azolla sp.) sebagai Pupuk pada Pertanian Organik - Faturrahman Hakim; Bunga Q Ramadhanti; Itsar H Wafi; Revi A Yulinda; Rizka Melisanti; Shafiyah Shafiyah; Firdaus Sulaiman (Seminar Nasional Lahan Suboptimal, 2021)
Hakim F, Ramadhanti BQ, Wafi IH, Yulinda RA, Melisanti R, Shafiyah S, Sulaiman F. 2021. Potential of combination of water hyacinth (Eichhornia Crassipes) and Azolla (Azolla sp.) as Fertilizer in Organic Agriculture. In: Herlinda S et al. (Eds), Prosiding Seminar Nasional Lahan Suboptimal Ke-9 Tahun 2021, Palembang 20 oktober 2021. pp. 587-594.  Palembang: penerbit  dan percetakan Universitas Sriwijaya (UNSRI). The purpose of this literature study was to examine whether the addition of azolla to water hyacinth compost has the potential to increase N nutrients in water hyacinth compost. The methodology was carried out by reviewing research results from various scientific journal literature. The result, that the nutrient content of water hyacinth compost has a total N element of 1.3%, while according to other studies, the total N nutrient content in water hyacinth compost is (1.58-1.75%), then Azolla plants have a total N content of 2.77% while in other studies showed that the total N content of azolla was 2.57%. The conclusion, combining water hyacinth with azolla has the potential to increase N nutrients in water hyacinth compost.